Imaginative Experience: A Narrative-Dialogic Ethnography of the Community Who Adores Its Idol - Ardianto, Eka (Gadjah Mada International Journal of Business, 2007)
Managing customer loyalty becomes an important activity in marketing management. One of the reasons is that loyal consumers tend to make good financial performances to producer. Unfortunately, gaining a loyal customer is not a trivial activity since there are gaps to understand consumer experience comprehensively. To fulfill the gaps, this article explores imaginative experience of the community who adores its idol in the light of cultural perspective. The members of the community who adores its idol experience the imaginative experience. The author argues that those phenomena are cultural perspective, because they are meaningful to the members. Through narrative-dialogic ethnography, the author builds the concept of imaginative experience that through the imaginative media, the members do narrative-dialogic between âthe realm of arealâ and âthe realm of afotikâ then activate the imaginative relations in âthe realm of aktinikâ. Every member constructs its imaginative relations into imaginative constructions formed in a personal story. Managing imaginative experience could benefit the company. It can be the âImaginative Experience Managementâ (IEM) that accommodates imaginative consumersâ experiences with the companyâs products deeply and sustainably through managing the story of its consumersâ imaginative experiences. It can also be linked to the customer loyalty programs. In this matter, IEM should be integrated with brand management.